Possible Effects on VA Outpatient Care of Expanding Medicaid: Implications of Having Access to Overlapping Publicly Funded Health Care Services. Issue 5 (15th April 2021) - O'Mahen, Patrick N; Petersen, Laura A
ABSTRACT: Background: Because veterans who use Veterans Health Administration (VA) health care retain VA eligibility while enrolling in Medicaid, increasing Medicaid eligibility may create improved health system access but also create unique challenges for the quality and coordination of health care for veterans. We analyze how pre-Affordable Care Act (ACA) state Medicaid expansions influence VA and Medicaid-funded outpatient care utilization. Materials and Methods: This study uses Difference-in-difference analysis to evaluate association between pre-ACA 2001 Medicaid expansions and VA utilization in a natural experiment. Veterans aged 18-64 years living in a study state during the study period were the participants. Dependent variables included participants' proportion of outpatient care received at the VA, whether a participant recorded care with both Medicaid and the VA, and total outpatient utilization. We analyzed changes between two states that expanded Medicaid in 2001 against three similar states that did not from 1999 to 2006. We adjusted for age, non-White race, gender, disease burden, and distance to VA facilities. This study was approved by the Baylor College of Medicine Institutional Review Board (IRB), protocol number H-40441. Results: In total, 346, 364 VA-enrolled veterans lived in the five study states during the time of our study, 70, 987 of whom were enrolled in Medicaid for at least 1 month. For low-income veterans, Medicaid expansion was associated with a 2.88 percentage-point decline in the VA proportion of outpatient services (99% CI −3.26 to −2.49), and a 2.07-point increase (1.80 to 2.35) in the percentage of patients using both VA and Medicaid services. Results also showed small increases in total (VA plus Medicaid) annual per-capita outpatient visits among low-income veterans. We estimate that this corresponds to an annual reduction of 80, 338 VA visits across study states (66, 155-94, 521). Conclusions: This study shows usage shifts when Medicaid expansion allows veterans to gain access to non-VA care. It highlights increased potential for care-coordination challenges among VA patients as states implement ACA Medicaid expansion and policymakers consider additional public health insurance options, as well as programs like CHOICE and the MISSION Act that increase veteran choices of traditional VA and community care providers.